2020
DOI: 10.1016/j.sopen.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of valued obstetric and gynecologic (OB/GYN) procedures in resource-poor areas

Abstract: Background Obstetric and gynecologic procedures are valuable in rural settings. Data identifying common procedures may better prepare surgeons to meet patient needs in remote settings. Materials and methods A literature review using key MeSH terms was performed according to methods described by the Cochrane Collaboration and PRISMA on studies that described obstetric and gynecologic surgery in rural high-income countries or any setting in middle- to low-income countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In general, compared to men, women are less likely to participate in shared decision-making or to choose the type of surgical procedure [12]. The quantity and quality of information available pertaining to surgical procedures and preoperative counseling is less optimal when proposing to perform surgery on women.…”
Section: Women Around the World Have Hi G Her Barrier S To Surg I C A...mentioning
confidence: 99%
“…In general, compared to men, women are less likely to participate in shared decision-making or to choose the type of surgical procedure [12]. The quantity and quality of information available pertaining to surgical procedures and preoperative counseling is less optimal when proposing to perform surgery on women.…”
Section: Women Around the World Have Hi G Her Barrier S To Surg I C A...mentioning
confidence: 99%
“…[6] A recent systematic review and meta-analytical study reported that in resource poor countries, O&G procedures made up 19% of all surgical cases. [7] Most common O&G surgeries are usually CD, followed by myomectomy. [7] The aim of the study was to determine the pattern of surgical procedures in Obstetrics and Gynecology at Rasheed Shekoni Federal University Teaching Hospital (RSFUTH) Dutse Nigeria over a 3 year period.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Most common O&G surgeries are usually CD, followed by myomectomy. [7] The aim of the study was to determine the pattern of surgical procedures in Obstetrics and Gynecology at Rasheed Shekoni Federal University Teaching Hospital (RSFUTH) Dutse Nigeria over a 3 year period.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy is the second most common surgery for women after cesarean section and the abdominal removal of the uterus is the most commonly used method by surgeons. 1 Hysterectomy can also be done through the vagina or as a laparoscopic or robot-assisted surgery. Regardless of the type of surgery used, hysterectomy is a major surgical procedure and studies have shown that these kind of major surgical trauma promotes an immunologic dysfunction that predisposes the patient to significant morbidity.…”
Section: Introductionmentioning
confidence: 99%